Caseous Intracardiac Calcification: A Diagnostic Enigma - Simon G. Findlay; Nicholas M. Child; Douglas F. Muir (Case Reports in Cardiology)
Intramyocardial calcification is a rare phenomenon often only discovered on postmortem. We describe the case of a healthy 69-year-old lady diagnosed with idiopathic caseous intracardiac calcification extending from the mitral valve annulus. We present high-quality images and propose an investigatory template for future cases.